Implementasi Wireless Sensor Network Mengunakan Babel Routing Protokol - Muhammad Rosyid Khulafa; Sabriansyah Rizqika Akbar; Gembong Edhi Setyawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
One of the technological development of wireless communication is Wireless. Currently developed into Wireless Sensor Network (WSN). A technology consisting of nodes as scattered within the scope of the system using a wireless network. One of the utilization of WSN technology is for application implementation to know temperature, weather, distance in the surrounding environment, then can exchange data through network node node that has been connected. One of them is if there is damage to fixed communication, WSN can be applied as secondary communication or other planning, as communication network infrastructure which is expected to be used when main telecommunication infrastructure have problem that is using Mobile ad hoc network (Manet) technology applied to Wireless Sensor Network (WSN). Manet in other ways can be interpreted as collected nodes, then move random (dynamic), then generate a temporary network by not relying on the existing structure. By utilizing Beagleboneblack as a Manet node, WSN can be applied as a communication between nodes. Beagleboneblack is a mini-computer open source-hardware product with linux Angstrom ARM support, plus many pin headers, digital pins, analogs, pwm and others will be very powerful. In addition to using the default OS, we can also use Linux Beaglebone board OS like Debian 8.6. Sensors are installed on each node, so the Manet can be built as a mobile network.